Report on the implementation of the European Charter for small enterprises in the Western Balkans (OECD, 2008)
Small and medium enterprises (SMEs) are the backbone of Western Balkan economies but until recently received relatively little attention from policy makers. Governments focused on consolidating macroeconomic stabilization and the restructuring and privatization of large companies. The adoption in 2003 of the European Charter for Small Enterprises contributed to a change in policy perspective. The SME Policy Index 2007 presents the first comprehensive and comparative assessment of progress made in implementing the Charter. The assessment is based on the SME Policy Index, an analytical tool designed by the OECD Investment Compact and the European Commission, and uses collaborative benchmarking to measure progress in the ten dimensions of the Charter. Albania, Bosnia and Herzegovina, Croatia, FYR Macedonia, Montenegro, Serbia and UNMIK/Kosovo are assessed in this report.--Publisher's description.